Pengaruh Lama Perendaman Air Kelapa dan Aplikasi Pupuk Kilat terhadap Pertumbuhan dan Hasil Panen Kacang Hijau (Vigna radiata L.) - Halawa, Juliman; Zulfida, Ida; Harahap, Lutfi Henderlan (JURNAL AGROPLASMA, 2025)
This study aimed to evaluate the effect of coconut water seed soaking duration and flash fertilizer application on the growth and yield of mung bean (Vigna radiata L.). The experiment was conducted at the experimental field of the Faculty of Agriculture, Indonesian Community Development University, Medan, from May to August 2024. A Randomized Block Design (RBD) with two factors and three replications was employed. The first factor was coconut water soaking duration (0, 2, 4, and 6 hours), while the second factor was flash fertilizer application (0, 0.25, 0.5, and 1 cc/L). Observed parameters included plant height, number of leaves, flowering age, pod weight per plant, and pod weight per plot. Results indicated that a soaking duration of 6 hours (P3) had a highly significant effect on all observed parameters, producing the highest plant height, leaf number, and pod weight. Similarly, flash fertilizer at 1 cc/L (K3) promoted better vegetative and reproductive growth compared to other treatments. The interaction of P3K3 produced the best performance across growth and yield traits. These findings suggest that combining coconut water seed soaking for 6 hours with flash fertilizer application at 1 cc/L is an effective strategy to enhance mung bean productivity. Keywords: mung bean, coconut water, flash fertilizer, growth, yield